Third Five Year Plan of Gulbarga District Vol-III - Planning Commission (Planning Commission)
Until the Police Action in 1948, Gulharga formed a part of the Nizams Dominions. It attained the statue of full fledged District in 1873, with six Taluks. In 1883, two more Taluks, Andola (Jewargi) and Shorapur were added to it. After the abolition of the Jagirs, four more Taluks were created out of the adjoining Paigah Areas and added to the District. Thus, the District consisted of (12) Taluks with three administrative Sub Divisions, located at Gulbarga, Tandur and Yedgir. After the Re-organisation of States, in 1956, the two Telugu speaking Taluks, Tandur and Kodangal were transferred to Andhra Pradesh.
Government of Mysore